Career Development and Job Satisfaction: Investigating the Mediating Role of Emotional Exhaustion in Gen Z - Muhammad Harry Al Giffary; Ivan Ivan; Jubaedah Jubaedah (Green Publisher Indonesia, 2025)
Generation Z employees, characterized by unique workplace expectations and technological fluency, present distinct challenges for organizational management, particularly regarding career development and job satisfaction dynamics. This study examines how emotional exhaustion mediates the relationship between career development and job satisfaction among Gen Z workers in South Jakarta, Indonesia. Using simple random sampling, data were collected from 387 Gen Z employees (aged 18-40, predominantly 24-28 years) working across various sectors in South Jakarta. Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 was employed to test the hypothesized relationships. Results reveal that: (1) career development significantly and positively influences job satisfaction (β = 0.409, t = 6.544, p < 0.001); (2) career development significantly affects emotional exhaustion (β = 0.654, t = 34.027, p < 0.001); (3) emotional exhaustion significantly impacts job satisfaction (β = -0.598, t = 8.118, p < 0.001); and (4) emotional exhaustion significantly mediates the career development-job satisfaction relationship (indirect effect = 0.392, t = 7.586, p < 0.001). The model demonstrates strong explanatory power (R² = 0.728 for job satisfaction; R² = 0.631 for emotional exhaustion). These findings indicate that while career development enhances job satisfaction directly, it simultaneously generates emotional exhaustion, which negatively impacts satisfaction. For Gen Z employees specifically, organizations must balance career advancement opportunities with workload management, emotional support systems, and transparent communication to optimize satisfaction outcomes while mitigating burnout risks inherent in career progression demands.